Географія туристичних потоків Львівської області - Паньків, Наталія; Pankiv, Nataliya (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Розглянуто підхід до визначення поняття туристичного потоку, його типізаційних та структурних особливостей. Проаналізовано передумови виникнення та територіального скерування туристичних потоків Львівської області, зроблено акцент на основних туристичних центрах та районах, найпривабливіших із туристичного погляду. Встановлено співвідношення кількості іноземних туристів та готельних підприємств різних районів. The purpose of study is an analysis of tourist streams in Lviv region, which resulted in the need to define the essence of «tourist stream», the definition of conditions for development of tourism within the region of study, analysis of domestic tourism in the context of international tourist streams and Ukraine as a whole, the definition of territorial characteristics and the dynamics of travel streams, and so on. Lviv region is one of the outstanding provisions of the country in the presence of natural recreation and therapeutic resources, there are more than 4000 monuments of history and culture within it, much of which are concentrated in Lviv (over 2000). As a result of preconditions analysis of regional referral of tourist streams in Lviv region the focus is made on the main tourist centers and districts, with the most attractive tourist point of views. It was conducted the correlation of foreign tourists number and hotel enterprises in various areas. Thus, the most attractive from the tourist point of view are Skole, Pustomyty, Mostyska and Zovkva districts, where the largest number of accommodation establishments are concentrated (L’viv is not included). Also it was clarified the positive and negative aspects of the development of domestic tourism.
The Geography of Tourism Streams of Lviv Region
Keywords: туристичний потік; туристична привабливість; передумови розвитку туризму; територіальна відмінність; туристичні центри; готельні заклади; the tourist stream; the tourist attraction; the preconditions of tourism development; the territorial difference; the tourist centers and hotel enterprises